A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Development of Cell-Based Relative Potency Assays for Antibody-Based Therapeutic Drug Products Against Botulism - Timothy M. Piazza; Theresa L. Geurs; Serena K. Wolfe; Daniel Harding; Thomas A. Little; Ward C. Tucker (Toxicon, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Active breeding seabirds prospect alternative breeding colonies - Jelena Kralj; Aurore Ponchon; Daniel Oro; Barbara Amadesi; Juan Arizaga; Nicola Baccetti; Thierry Boulinier; Jacopo G. Cecere; Robin M. Corcoran; Anna-Marie Corman; Leonie Enners; Abram Fleishman; et al. (Oecologia, 2023)

Refining the risk of HTLV-1-associated myelopathy in people living with HTLV-1: identification of a HAM-like phenotype in a proportion of asymptomatic carriers - Daniel Harding; Carolina Rosadas; Sandra Maria Tsoti; Amanda Heslegrave; Molly Stewart; Peter Kelleher; Henrik Zetterberg; Graham P. Taylor; Divya Dhasmana (Journal of NeuroVirology, 2022)
Up to 3.8% of human T-lymphotropic virus type-1 (HTLV-1)-infected asymptomatic carriers (AC) eventually develop HTLV-1-associated myelopathy (HAM). HAM occurs in patients with high (> 1%) HTLV proviral load (PVL). However, this cut-off includes more than 50% of ACs and therefore the risk needs to be refined. As HAM is additionally characterised by an inflammatory response to HTLV-1, markers of T cell activation (TCA), β 2 -microglobulin (β 2 M) and neuronal damage were accessed for the identification of ACs at high risk of HAM. Retrospective analysis of cross-sectional and longitudinal routine clinical data examining differences in TCA (CD4/CD25, CD4/HLA-DR, CD8/CD25 & CD8/HLA-DR), β 2 M and neurofilament light (NfL) in plasma in ACs with high or low PVL and patients with HAM. Comparison between 74 low PVL ACs, 84 high PVL ACs and 58 patients with HAM revealed a significant, stepwise, increase in TCA and β 2 M. Construction of receiver operating characteristic (ROC) curves for each of these blood tests generated a profile that correctly identifies 88% of patients with HAM along with 6% of ACs. The 10 ACs with this ‘HAM-like’ profile had increased levels of NfL in plasma and two developed myelopathy during follow-up, compared to none of the 148 without this viral-immune-phenotype. A viral-immuno-phenotype resembling that seen in patients with HAM identifies asymptomatic carriers who are at increased risk of developing HAM and have markers of subclinical neuronal damage.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Diversity in the population of Fusarium graminearum isolated from wheat and corn in Alberta, Canada - Hafiz Ahmed; Qixing Zhou; Kher Zahr; Yalong Yang; Heting Fu; Alian Sarkes; Yingli Wang; Krista Zuzak; David Feindel; Greg C. Daniels; Michael W. Harding; Jie Feng (Journal of Plant Diseases and Protection, 2020)

Stream biomonitoring using macroinvertebrates around the globe: a comparison of large-scale programs - Daniel F. Buss; Daren M. Carlisle; Tae-Soo Chon; Joseph Culp; Jon S. Harding; Hanneke E. Keizer-Vlek; Wayne A. Robinson; Stephanie Strachan; Christa Thirion; Robert M. Hughes (Environmental Monitoring and Assessment, 2015)

Naphthalene Biomarkers and Relationship with Hemoglobin and Hematocrit in White, Black, and Hispanic Adults: Results from the 2003–2004 National Health and Nutrition Examination Survey - Daniel L. Sudakin; Ellen Smit; Andres Cardenas; Anna Harding (Journal of Medical Toxicology, 2013)

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”

Evaluating the Effectiveness of Predator Control: the Non‐Native Red Fox as a Case Study - Elaine K. Harding; Daniel F. Doak; Joy D. Albertson (Conservation Biology, 2001)
Non‐native vertebrate predators pose a severe threat to many native species, and a variety of management programs are aimed at reducing predator effects. We sought to assess the effects of predator‐control programs by analyzing changes in prey and predator populations based on data commonly collected in these programs. We examined data from a predator‐control program that primarily targets the introduced red fox ( Vulpes vulpes regalis ) in central California. Red foxes negatively affect populations of native waterbirds, particularly the endangered California Clapper Rail ( Rallus longirostris obsoletus ). Using a combination of matrix population modeling, simple difference equations, and statistical analysis, we analyzed data on removed predators and monitored prey populations. Past control efforts succeeded in depressing fox numbers in local areas over 3‐month intervals, and there was a significant, positive relationship between the growth rate of local Clapper Rail populations and the successful trapping of red foxes in the preceding year. By modeling the effect of different fox‐removal rates, we found that a stable or declining population could be achieved by removing a minimum of 50% of the adults and 25% of the juveniles. Under trapping rates of 50–70%, the proportion of the fox population composed of immigrants averaged 20–52%. In contrast to the current management approach, elasticity analyses suggested that changes in adult survival rates had relatively little effect on long‐term population growth. Overall, our approach indicated that predator control was effective in the short term, but for longer‐term success it may be necessary to redirect efforts to control juvenile and immigrant foxes. Our analytical approach is potentially useful for evaluating current control programs aimed at reducing the effects of predators on native species.

Incompatible pathogen infection results in enhanced reactive oxygen and cell death responses in transgenic tobacco expressing a hyperactive mutant calmodulin - Scott A. Harding; Daniel M. Roberts (Planta, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)